2015
DOI: 10.1016/j.seizure.2015.08.010
|View full text |Cite
|
Sign up to set email alerts
|

GSTA1, GSTM1, GSTP1 and GSTT1 polymorphisms in progressive myoclonus epilepsy: A Serbian case–control study

Abstract: GSTT1-null genotype might be associated with the increased risk and enhanced susceptibility to oxidative stress in PME patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 39 publications
1
17
1
Order By: Relevance
“…It is also interesting to outline that almost half of the proteins that are differentially expressed in EPM1‐derived organoids and enriched in radial glial cells are involved in different types of human epilepsies. For instance, Collagen COL11A1 mutated in the Stickler syndrome, caused by mutations in COL2A1 or COL11A1, is associated with epileptic phenotypes (Savasta et al , ; Zhou et al , ); IFITM3 (interferon‐induced transmembrane protein 3) has been identified among genes that are target of epilepsy‐associated miRNA in animal models and human tissues (Cava et al , ); heterozygous mutation in GLUD1 gene has been reported in patients affected by hyperinsulinism, commonly associated with epileptic seizures (Aka et al , ); RRAS (Guo et al , ) and MGST1 (Shang et al , ; Ercegovac et al , ) are associated with epilepsy risk.…”
Section: Discussionmentioning
confidence: 99%
“…It is also interesting to outline that almost half of the proteins that are differentially expressed in EPM1‐derived organoids and enriched in radial glial cells are involved in different types of human epilepsies. For instance, Collagen COL11A1 mutated in the Stickler syndrome, caused by mutations in COL2A1 or COL11A1, is associated with epileptic phenotypes (Savasta et al , ; Zhou et al , ); IFITM3 (interferon‐induced transmembrane protein 3) has been identified among genes that are target of epilepsy‐associated miRNA in animal models and human tissues (Cava et al , ); heterozygous mutation in GLUD1 gene has been reported in patients affected by hyperinsulinism, commonly associated with epileptic seizures (Aka et al , ); RRAS (Guo et al , ) and MGST1 (Shang et al , ; Ercegovac et al , ) are associated with epilepsy risk.…”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy is a disease of the brain, the distinctive characteristic of which is a predisposition to generate unprovoked seizures 59 . The association between polymorphisms of GST genes and the risk of epilepsy has been investigated in several studies 60 62 . In patients with progressive myoclonus epilepsy, a GSTT1 -null genotype has been associated with increased risk of developing the disease where it might contribute to enhanced susceptibility to oxidative stress 60 .…”
Section: Gsts Gene Polymorphisms and Correlation To Diseasesmentioning
confidence: 99%
“…The association between polymorphisms of GST genes and the risk of epilepsy has been investigated in several studies 60 62 . In patients with progressive myoclonus epilepsy, a GSTT1 -null genotype has been associated with increased risk of developing the disease where it might contribute to enhanced susceptibility to oxidative stress 60 . Different results were obtained in other group of patients 61 .…”
Section: Gsts Gene Polymorphisms and Correlation To Diseasesmentioning
confidence: 99%
“…Finally, the result demonstrated influence of Ala16Val MnSOD polymorphism, mainly of VV genotype in epilepsy patients. Accordingly, studies have shown that the polymorphism of some genes may be related to the efficacy, tolerability, and action of antiepileptic drugs [48,49].…”
Section: Resultsmentioning
confidence: 99%